2016
DOI: 10.1007/s11663-016-0606-0
|View full text |Cite
|
Sign up to set email alerts
|

Initial Wetting and Spreading Rates Between SiC and CaO-SiO2-MnO Slag

Abstract: The wetting of CaO-SiO 2 -MnO slag on silicon carbide was studied with a variety of slag compositions at 1823 K (1550°C). Wetting experiments were performed by the dispensed drop technique. We observed complete wetting of the slag on SiC (within 1 second) without a bubble reaction regardless of the basicity (=CaO/SiO 2 = C/S ratio). However, after 8 seconds, the bubble reaction was observed under conditions of C/S = 0.8 and 1.1, whereas it was not observed at temperatures lower than 1823 K (1550°C). The contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Park et al . [19] carried on the wetting experiments of CaO–SiO 2 –MnO on SiC by the dispensed drop technique. The results showed that molten CaO–SiO 2 –MnO slags have good wettability on SiC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al . [19] carried on the wetting experiments of CaO–SiO 2 –MnO on SiC by the dispensed drop technique. The results showed that molten CaO–SiO 2 –MnO slags have good wettability on SiC.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the wetting angle changes from 20°to 73°in Ar and from 58°to 87°in a CO atmosphere. Park et al [19] carried on the wetting experiments of CaO-SiO 2 -MnO on SiC by the dispensed drop technique. The results showed that molten CaO-SiO 2 -MnO slags have good wettability on SiC.…”
Section: Influences Of Temperature On Relative Viscositymentioning
confidence: 99%
“…Generally, the corrosion resistance of refractory can be roughly estimated by measuring the contact angle between slag and refractory. [25][26][27] Liu et al 28 studied the wetting and erosion behavior between slag with different alkalinity and MgO-C refractories by using the sessile drop method. The results show that the higher the alkalinity of the slag, the weaker the corrosion of the slag on MgO-C refractories.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion behavior between slag and refractory is closely related to the wettability between the two phases. Generally, the corrosion resistance of refractory can be roughly estimated by measuring the contact angle between slag and refractory 25–27 . Liu et al 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have conducted studies on wetting between solid ceramic substrates and liquid slags. [5][6][7][8][9][10][11][12][13][14][15] Wetting studies using SiO 2 have also been conducted, but not with liquid slag. [16][17][18] Many factors affect the contact angle, including the solubility of the two materials.…”
Section: Introductionmentioning
confidence: 99%